Standar Keselamatan dan Kesehatan Kerja (K3) Wisma Arimbi dan Wisma Bima Rumah Sakit Jiwa Grhasia Daerah Istimewa Yogyakarta - Julian Dwi Saptadi; Machfudz Eko Arianto; Muhammad Rafly Adha (Jurnal Health Sains, 2021)
The implementation of hospital occupational health and safety service standards at Wisma Arimbi and Wisma Bima is still not optimal because there are still hospital occupational health and safety programs that have not been running optimally, such as uneven health checks. The purpose of this study was to see the application of occupational safety and health service standards at Wisma Arimbi and Wisma Bima in the Grhasia Mental Hospital, Special Region of Yogyakarta. This is a qualitative research with a case study approach. The sampling technique in this study was to use purposive sampling method with as many as 5 subjects. The data in this study were obtained from in-depth interviews. The safety and security of Wisma Arimbi and Wisma Bima are good. The hospital has a hospital occupational health and safety team, adequate PPE and a good working environment. However, there is a shortage of hospital occupational health and safety human resources where only one person is competent in the hospital occupational health and safety field, while other members have other main tasks (double jobs). Occupational Health Services at Wisma Arimbi and Wisma Bima are already in operation, such as providing additional food, sports facilities and health insurance. But the health check has not been maximal. The implementation of service standards at Wisma Arimbi and Wisma Bima has not been maximal, there are still some hospital occupational health and safety service standards programs that have not yet been implemented, such as uneven health checks, lack of fire protection facilities, and lack of competent officers in the OSH sector.